Sustainable agriculture and food security in Africa: An overview - Linda Kleemann (Kiel Institute for the World Economy (IfW), 2012)
The development of the agricultural sector and the improvement of the food security situation are seen as essential components to sustainable development in Africa. However, continuing population growth, impacts of climate change and environmental degradation add to an unprecedented combination of pressures that threaten existing efforts and solutions. This article discusses the challenges of meeting the food security needs in a sustainable way. Due to its involvement of all three dimensions of sustainable development, economic, social and ecological, we argue that organic farming could be one possible approach to create a more sustainable agricultural system.
Keywords: O13; Q01; Q56; 330; sustainability; organic agriculture; food security